Exploring Maritime Education's Role In Global Trade and Workforce Development - Damoyanto Purba; Erwin Ferry Manurung; Devananda Vincensius Siregar; Junian Budi Argo; Jaja Suparma; Joko Subekti; Hotman Tua Pangaribuan (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This research investigates the effectiveness of maritime education in developing a skilled workforce capable of facilitating global trade and economic development. Through qualitative analysis of the perspectives and experiences of maritime professionals, lecturers, and graduates, the study examines key areas including curriculum alignment, workforce competency development, technological integration, and sustainability. The findings reveal that while maritime education is effective in providing core technical skills, gaps exist in the integration of emerging technologies and environmental practices. Addressing these gaps by updating curricula to emphasize innovation and sustainability will better prepare graduates to meet the future challenges of the maritime industry. The research highlights the critical role of maritime education in shaping the next generation of industry leaders who can contribute to global trade efficiency and environmental stewardship.